Land use changes and bird diversity in subtropical forests: urban development as the underlying factor - Silvetti, Luna Emilce; Gavier Pizarro, Gregorio Ignacio; Solari, Laura María; Arcamone, Julieta Rocio; Bellis, Laura Marisa (Springer, 2022)
The Serrano Chaco forest is the least extended Gran Chaco forest type with a long his tory of human disturbances, such as ranching, urbanization, fires, an exotic tree species expansion, which have altered natural vegetation and, therefore, the resources available for avifauna. However, the impact of these disturbances on Serrano forest birds has re ceived little attention. Here, using functional and taxonomic approaches, we explored the environmental, topographical and anthropogenic factors determining bird community structure in the Serrano forests at different spatial scales (<250 m 500- and 1000-m). We used a combination of satellite imagery-based data and field sampling. We identified three ecological groups of birds: forest specialist, understory specialist and generalists, and classified them into functional groups according to life history traits and habitat use. We found that the response to landscape structure varied with the spatial scale and bird group; however, urban development and exotic trees forest occurrence were consistently present among the main factors reducing functional and taxonomic diversity of forest and understory birds. At the 1000-m scales, forest specialist birds tended to disappear from the areas with dense urbanization in areas with low percentage of Serrano forest. In landscape dominated by L. lucidum, forest understory birds tended to disappear. In all cases, generalist species expanded towards those areas. Our results indicate that the func tional roles of avifauna are being greatly modified, potentially affecting forest ecosystem functioning. Restoration strategies must be implemented to preserve the last remnants of Serrano forest.